The Transformations of Tarawangsa Traditional Music in the Ritual Ceremony of Bubur Syura in Sukaluyu Village, Sumedang, West Java, Indonesia - Supriatna, Nanang (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: There are various art forms in West Java, starting from dances, music, fine arts, to theater. Based on the research results, it was found that there were more or less 300 types of arts spread in various cities and regencies. However, some of them are âdyingâ, or in a âseverely criticalâ condition, and some have even disappeared. In other words, the traditional arts of West Java have dwindled in number, even the existing arts are in the danger of extinction. Among these âdyingâ arts, there are still some that thrive and continue to be loved by the supporting communities. One of the surviving arts is the âtarawangsaâ traditional music developed in Sumedang area, especially in Sukaluyu region, Girimukti Village Administrative, North Sumedang District, Sumedang Regency, West Java, Indonesia. Meanwhile, there has not been much in-depth research on local wisdom, ultimately in the domain of traditional music. Hence, this paper would like to discuss one of the research outcomes concerning the transformations of âtarawangsaâ traditional music. The issues covered include: âtarawangsaâ songs, the âlarasâ (scale) played, and its development in Sukaluyu Village, Girimukti Administrative Village, Sumedang Regency, West Java, Indonesia. Based on the research results, there are two important assumptions: firstly, the transformations of âtarawangsaâ traditional music are immanent in nature, namely they happen because of the creative process of the artists; and secondly, the transformations take place because there is contact between Sukaluyu artists and other area artists. KEY WORDS: Transformation, âtarawangsaâ traditional music, ritual, local wisdom, Sumedang area, and creative process of the artists.About the Author: Nanang Supriatna is a Senior Lecturer at the Department of Music Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. The author can be contacted via e-mail at: supriatna61@yahoo.comHow to cite this article? Supriatna, Nanang. (2015). âThe Transformations of Tarawangsa Traditional Music in the Ritual Ceremony of Bubur Syura in Sukaluyu Village, Sumedang, West Java, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.189-196. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (November 12, 2014); Revised (February 17, 2015); and Published (April 28, 2015).